Prawda o Bogu Stwórcy, stworzeniu i jego odnowie, według "Wyznań" św. Augustyna - Zarzycki, Stanisław (Vox Patrum, 2019)
This article raises the theme of creation, which, besides the philosophical question of seeking truth and theological-spiritual confessio, is one of the main issues of Augustine’s Confessions. First, it indicates the importance of this issue in this work and is looking for a way to connect it with two thematically different parts of Confessions, autobiographical and exegetic. Next, he shows Augustine’s “winding road” of seeking the truth about the Creator and creation, leading through the time of youth’s mistakes and the period of getting lost in the Manichean sect (Materialism, the metaphysical Dualism). He also explains affecting Augustine, under the influence of Neoplatonism, the experience of “returning to himself” and gaining the light of the truth about the Creator and creation, and then attaining, under the influence of readings of the Word of God, the grace of conversion as a gift of the “new creation”. In the last part of the article, the author, based on the last books of Confessions, makes more familiar the theology and spirituality of the “new creation” explained in a literal and allegorical sense.